Trends in hospital admissions for adrenal insufficiency in adolescents and young adults in the 21st century - Chrisp, Georgina L.; Quartararo, Maria; Torpy, David J.; Falhammar, Henrik; Rushworth, R. Louise (Frontiers in Endocrinology, 2022)
Abstract Background: Very little is known about the epidemiology of adrenal crises (AC) and adrenal insufficiency (AI) in adolescents and young adults. Methods: Data on all admissions to Australian hospitals between 2000/1 to 2019/20 for a principal diagnosis of AI (including AC) in 10-24 year olds were extracted from a national repository. Age and sex specific rates and age adjusted rates were compared. Findings: Over the study, there were 3386 admissions for a principal diagnosis of AI; 24.0% (n=812) were for an AC and 50·7% (n=1774) were for secondary AI. Age-adjusted AI admissions increased from 31·70/million in 2000/1 to 54·68/million in 2019/20 (p<0·0001). Age-adjusted AC admissions also increased, most notably in the second decade (from 5·80/million in 2010/11 to 15·75/million in 2019/20) (p<0·00001). Average AI and AC admission rates were comparable between the sexes, but rates increased significantly in females, especially in those aged 20 to 24 years, whose AC rate in 2019/20 (39·65/million) was significantly higher than the corresponding rate in 2000/1 (3·15/million) (p<0·00001). Average age-adjusted SAI admission rates were higher in males (23·92/million) than females (15·47/million) (p<0·00001). However, SAI admission rates increased only among females (from 11·81/million to 22·12/million in 2019/20), with an increase in 20-24 year old females in the second decade from 5·07/million in 2010 to 20·42/million (p<0·00001). Age adjusted admissions for congenital adrenal hyperplasia, primary AI (PAI) and drug-induced AI did not change significantly over the study. Interpretation: AC/AI admissions increased over the first two decades of this century in the emerging adult population, particularly among females who also experienced a marked increase in AC admission rates, most evident in the second decade. Although uncertain, possible explanations include: dose of glucocorticoid replacement; non-adherence to therapy; psychosocial factors; and difficulty in transition to adult services. Admissions for SAI also increased, while rates of PAI, CAH remained constant.